Lexicon of a summer calendar-ceremonial cycle in the Belarusian and Ukrainian languages (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
In the article the summer calendar-ceremonial traditions of east Slavs are defined, the names of a summer calendar-ceremonial cycle in the Belarusian and Ukrainian languages are analyzed, their lexicon-thematic, semantic and genetic characteristics are described and the general and specific features are called.
Keywords: calendar-ceremonial lexicon; a ceremony; tradition; a summer cycle; a holiday